Highly adsorption of alginate/bentonite impregnated TiO2 beads for wastewater treatment: Optimization, kinetics, and regeneration studies - Zainab D. Alhattab; Aseel M. Aljeboree; Mohammed Abed Jawad; Fatime Satar Sheri; Ahmed Kareem Obaid Aldulaim; Ayad F. Alkaim (Caspian Journal of Environmental Sciences)
In this work, we prepared an eco-friendly, simple, stable new adsorbent SA-Bn-TiO2 NPs hydrogel and Comparative between SA-Bn-TiO2 NPs, SA-Bn, and TiO2 NPs surfaces as adsorbents. The best results of the percentage of removal (E%) of two pollutants including Amoxicillin (AMX) and 4-chlorophenol (CPH) arranged in the order of increasing as SA-Bn-TiO2 NPs > SA-Bn > TiO2 NPs. The good results of the percentage of removal (E%) of SA-Bn-TiO2 NPs were 87.56% and 82.56 for AMX and CPH at the same order. Kinetics adsorption models of two pollutants on SA-Bn-TiO2 NPs was studied and modelled utilizing three adsorptions kinetic. The classification of the kinetic models according to the simulation of the adsorption study is pseudo first order < pseudo-second order > chemisorption. Recyclability and desorption studies indicated the better reusing performance of the prepared composite. Based on the results, the prepared nano-composites can be useful as a promising, cost-effective, environmentally friendly, and efficient material for pollutant decontamination. Studies was carried out utilizing several desorption agents at various concentrations (0.01, 0.05 and 0.1 N) including HNO3, H2SO4, HCl, NaOH, H3PO4, ethanol, acetone and water. The SA-Bn-TiO2 NPs was regeneration with 100% using water.